2004
DOI: 10.17221/4268-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The effect of digitonin on egg quality, cholesterol content in eggs, biochemical and haematological parameters in laying hens

Abstract: Digitonin is a plant steroid that belongs to steroids sapogenin, C 27 -steroid. Digitonin contains 1 mol of digitogenin, 2 mols of glucose and 1 mol of xylose. Saponins in complex with cholesterol and other 3 β-hydroxysterols form molecular compounds such as cholesterol digitonide. Digitonin and its analogues damage liposomal elements of plasma membranes and cause haemolysis of red cells. These compounds activate granulocytes as well (Nishikawa et al., 1984;Sancho et al., 1993). Clarke and Hillard (1981) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…The lowest value (1.21 mmol/1) was found in helmeted guineafowl while the highest value was detected in wild turkey (5.93 mmol); this value is outside the range of mean values observed in other species and fails to fall in the range of 5.02-18.92 mmol/l reported by Meluzzi et al (1992). Tůmová et al (2004) reported the mean value of 3.47 mmol/l. Other authors point out the differences in the concentrations of CHOL and TAG in different hybrids, depending on gender (higher in males as compared to females) and age where the concentration of CHOL decreases and the concentration of TAG increases (Meluzzi et al 1992;Straková et al 1993).…”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…The lowest value (1.21 mmol/1) was found in helmeted guineafowl while the highest value was detected in wild turkey (5.93 mmol); this value is outside the range of mean values observed in other species and fails to fall in the range of 5.02-18.92 mmol/l reported by Meluzzi et al (1992). Tůmová et al (2004) reported the mean value of 3.47 mmol/l. Other authors point out the differences in the concentrations of CHOL and TAG in different hybrids, depending on gender (higher in males as compared to females) and age where the concentration of CHOL decreases and the concentration of TAG increases (Meluzzi et al 1992;Straková et al 1993).…”
Section: Resultscontrasting
confidence: 51%
“…In addition, the collection samples of biological material and the methods of laboratory analysis also play an important role (Meluzzi et al 1992). Partial results of biochemical screening in gallinaceous poultry (the order Galliformes), namely hens, are reported in papers by Jeřábek et al (1993), Suchý et al (2004) and Tůmová et al (2004), or in broiler chickens by Meluzzi et al (1992), Straková et al (1993), Itoh et al (1995) and others. However, similar data in feathered game is only sporadic.…”
mentioning
confidence: 99%
“…The lowest concentration of cholesterol, which is an indispensable precursor for synthesis of many important steroid hormones, was 2.67 mmol/l in BPR line. Higher values of plasmatic cholesterol were observed by Tůmová et al (2004) in laying hens. The level of creatinine in blood plasma was another parameter involved in our study because in poultry it reflects the supply of N-compounds.…”
Section: Resultsmentioning
confidence: 85%
“…The dynamics of selected biochemical parameters in the blood plasma of layers was studied by a number of authors. Molar concentrations of plasma cholesterol were reported for example by Máchal (2000), who found that mean levels of cholesterol during egg laying ranged from 2.52 to 4.12 mmol/l, while Tůmová et al (2004) reported the range of 3.40-7.53 mmol/l, Suchý et al (1999) the range of 2.73-6.18 mmol/l, and Lichovníková et al (2002) the range of 3.56-3.57 mmol/l. Some authors, for example Puvadolpirod and Thaxton (2000), related the level of plasma cholesterol in layers to stress as Pavlík et al (2004) did in the case of plasma glucose.…”
mentioning
confidence: 84%
“…These results are in good agreement with haematological findings by Straková et al (2001), who showed that during egg laying the count of erythrocytes dropped from 2.51 T/l to 2.16 T/l, haematocrit levels from 0.29 l/l to 0.26 l/l and the content of haemoglobin from 92.52 g/l to 75.29 g/l. Tůmová et al (2004) reported increased levels of total erythrocyte count in the blood of control layers (3.15 T/l) in comparison with experimental layers (2.88 T/l and 2.83 T/l) which were administered digitonin. Mean leukocyte counts ranged according to the above authors as follows: 17.65 G/l, 18.41 G/l, and 16.59 G/l.…”
mentioning
confidence: 88%